Design of Multicatalytic Systems Through Self-Assembly - Fernandes, Antony E.; Jonas, Alain M. (Catalysts, 2025)
The development of self-assembled multicatalytic systems has emerged as a promising strategy for mimicking enzymatic catalysis in synthetic systems. This approach leverages the use of non-covalent interactions, such as hydrophobic interactions, hydrogen bonding, metal–ligand coordination, and aromatic stacking, to organize multiple catalytic centers within a defined, cooperative framework, allowing for enhanced reactivity, selectivity and efficiency, akin to the behavior of natural enzymes. The versatility of this approach enables the modular design, preparation, screening and optimization of systems capable of concerted catalysis and dynamic adaptation, making them suitable for a wide range of reactions, including asymmetric synthesis. The potential of these systems to emulate the precision and functionality of natural enzymes opens new avenues for the development of artificial multicatalytic systems with tailored and adaptable functions.